Diseño de un material de enseñanza con coherencia intracurricular sobre el proceso de la nutrición humana (2020)
This research work aims to design a teaching material with intracurricular coherence from the formulation of specific domain theories on the process of human nutrition, for the last level of elementary school. In this way, it is intended to overcome some teaching and learning difficulties related to the fragmentation of knowledge and the lack of curricular coherence. To achieve this objective, a theoretical framework was developed that guided the alignment of design elements and allowed guiding the construction and design of innovative learning environments with curricular coherence towards a comprehensive and articulated understanding of the process of human nutrition. From these theoretical references, a qualitative methodology informed by the content analysis of different documentary references was taken into account through the Content Representation (CoRe) methodological instrument. Finally, through this instrument, the curricular and methodological decisions were made to obtain as a result the formulation of a set of specific domain theories and, based on these theories, build a teaching material with curricular coherence on the process of human nutrition. for the fifth grade of primary. This TIC-powered teaching material is in a digital format that contains an interface or platform, the student's booklet, the support material and the CoRe. The conclusions of this research allow us to recognize the importance of overcoming the lack of coherence and the fragmentation of knowledge in the design of learning environments.